The Effect of Fear of Missing Out (FoMO) and Peer Conformity on Impulsive Buying in Semarang City Students (Study on TikTok Shop Consumers) - Gaiska Meindieta Muharam; Dewi Sulistiya; Novita Sari; Khairani Zikrinawati; Zulfa Fahmy (LPPM Institut Studi Islam Sunan Doe, 2024)
The purpose of this study was to find out how much influence 1) Fear Missing Out (FoMO) has on Impulsive Buying Shopping at the TikTok Shop 2) Peer Conformity towards Impulsive Buying Shopping at the TikTok Shop 3) Fear of Missing Out and Peer Conformity towards Impulsive Buying Shop at the TikTok Shop. Sampling in this study used an accidental technique. The number of samples taken using the Google Form was 114 participants. Collecting data in this study using a statement scale questionnaire. The results of the (partial) T test show that Fear of Missing Out has an effect on Impulsive Buying as indicated by a significance value of 0.001 <0.05. Likewise, the results of Peer Conformity analysis show that Impulsive Buying has a significance value of 0.000 <0.05. There are also results of the F test study showing a significance value of 0.000 <0.05 which means Fear of Missing Out and Peer Conformity simultaneously affect Impulsive Buying in Shopping at the TikTok Shop. Therefore, research proves that FoMo and Peer Conformity are very influential on impulsive buying in Semarang City students, indicated by an influence value of 52%.